Sickle cell disease in pregnancy. Issue 6 (June 2016) - Balachandren, Neerujah; Awogbade, Moji; Johns, Jemma
Abstract: Sickle cell disease (SCD) is a multisystem disease, in which pregnancy carries significant risks of maternal and perinatal morbidity and mortality. Women with SCD should have their pregnancies managed jointly by specialist obstetricians, midwives and haematologists. Within the UK, there is great geographical variation in the prevalence of SCD, with the highest prevalence in large urban centres. Trainee obstetricians practising outside these areas may not gain substantial experience in managing these patients and this review therefore aims to highlight the antenatal, intrapartum and postnatal management of pregnant women with SCD.